Mice Against Weasels, Humans and Frogs. On the Function of Contrast in Presenting Opponents and Creating Action in Batrachomyomachia - Zbądzki, Jakub (Contrasts in humanities: literature, language, culture, 2023)
The work aims to present how the author of Batrachomyomachia used the contrast to illustrate the differences between the sides of the battle in the poem (while also reaching for other creatures), which lead directly to the war. It was noticed that the contrast between them served as a casus belli: the differences underpin prejudices, and they determine the recognition of the accident as a deliberate attack on mice. There were also showed sources of humour based on contrasts: intertexts parodying the Greek epics or myths, and the construction of the catalogue of enemies, in which frogs take over the negative traits of usual mice foes.